Effect of Pineapple Pulp on Sensory Quality and Shelf-life of Pineapple Cake (Journal of Environmental Science and Natural Resources, 2015)
The experimental study on performance formulation and analysis of pineapple pulp fortified cake considering physical, chemical, sensorial and microbial quality. Cake was fortified with 5%, 10%, 15% and 20% pineapple pulp incorporated into wheat flour. The pineapple pulps used in the cake preparation were analyzed for proximate composition. The physical and chemical properties of cakes were analyzed. Quantitive microbial analysis of food samples were done on the basis of total viable count. Bacterial load range from 1.22×102(cfug-1) to 9.54×103(cfug-1) on different storage condition. Zero present pineapple pulp incorporated cake sample showed the highest microbial load 9.54×103(cfug-1).Total fungal count ranged from 0.97×102 to 5.04×103 (cfug-1)on different storage conditions. Fortified cake with 10% pineapple pulp contains lowest amount of fungi and bacteria after 8 days. So its shelf life will be enhanced about 6-7 days. Further 5%, 15%, and 20% pineapple pulp incorporated cake sample contain high microbial load, hence they will get shelf life of 5-6 days. Fortification of cake with 5%, 10%, 15%, 20%, pineapple pulp increasedthe value of ash, fiber and moisture in comparing with control cake. The statistical analysis of organoleptic test response of sensory attributes revealed that color, flavor, texture and overall acceptability were decreased with the increase of pineapple pulp in the cake formulation.Symmetry, crust and crumb quality, crust color and consistency,color,texture of the crumb and microbial load of the cakes containing 10% pulp were better than those of cakes containing above 10% pineapple pulp.J. Environ. Sci. & Natural Resources, 8(1): 7-11 2015